(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The study aimed to identify the concept and forms of hate speech, and the behavioral effects resulting from its spread and the role of social networking sites in combating hate speech and its impact on the system of societal and religious values, from the point of view of Hebron University students. To achieve the objectives of the study, the researcher relied on the analytical descriptive approach, and designed a study tool (questionnaire) that was distributed to a sample of (100) students from the Department of Mass Communication at Hebron University. The results of the study, find Social networking sites contribute to the dissemination of hate speech and exacerbate differences, as a large percentage of the respondents believed, and a medium percentage believed that it also works to call for dialogue and reduce violent and extremism speeches. Hate speech on social media has a great impact on the system of societal and religious values, as quarrels and disputes abound between people, leading to societal extremism and a decline in people’s commitment to religion and political values. Provoking strife among the components of society, the spread of division and rivalry, and the spreading and incitement of sectarian nervousness are among the behaviors resulting from the spread of hate speech on social networking sites to its users. There is a statistically significant relationship at the significance level (0.05) for the use of social networking sites and its impact on combating hate speech, from the point of view of Hebron University students.